Design patterns in modern C++20 : reusable approaches for object-oriented software design - Nesteruk, Dmitri (Apress, 2022)
Apply the latest editions of the C++ standard to the implementation of design patterns. As well as covering traditional design patterns, this book fleshes out new design patterns and approaches that will be useful to modern C++ developers. Author Dmitri Nesteruk presents concepts as a fun investigation of how problems can be solved in different ways, along the way using varying degrees of technical sophistication and explaining different sorts of trade-offs. Design Patterns in Modern C++20, Second Edition also provides a technology demo for modern C++, showcasing how some of its latest features (e.g., coroutines, modules and more) make difficult problems a lot easier to solve. The examples in this book are all suitable for putting into production, with only a few simplifications made in order to aid readability. What You Will Learn Use creational patterns such as builder, factories, prototype and singleton Implement structural patterns such as adapter, bridge, decorator, facade and more Work with the behavioral patterns such as chain of responsibility, command, iterator, mediator and more Apply functional design patterns such as the Maybe Monad Who This Book Is For This book is for both beginner and experienced C++ developers.